Summary of the agro-ecological and socio-economic context for the Cereal Systems Initiative for South Asia (CSISA) - Pede, Valerien; Ward, Patrick S.; Spielman, David J.; Paris, Thelma R. (International Rice Research Institute, 2012)
The Cereal Systems Initiative for South Asia (CSISA) Baseline Household Survey was conducted in late-2010 and early-2011 across eight of the hub domains in which CSISA was operating during its initial phase. The household survey was designed to inform CSISA management as well as to establish a priori conditions (farming practices, farmer livelihoods, etc.) against which the social, economic, and livelihood impacts of CSISA will be evaluated. Pursuant to these objectives, a structured questionnaire was developed in a joint effort of socio-economists from different centers of the Consultative Group on International Agricultural Research (CGIAR), as well as agronomists and hub managers. In all, the baseline household survey collected data on 2,628 households across the CSISA hub domains of Haryana, Punjab, eastern Uttar Pradesh, Bihar and Tamil Nadu in India; Dinajpur and Gazipur in Bangladesh; and the Terai region of central Nepal.